Commitment to build trust by socially responsible firms: Evidence from cash holdings - Chang, Ching-Hung; Chen, Sheng-Syan; Chen, Yan-Shing; Peng, Shu-Cing (Journal of Corporate Finance, 2019)
We show that socially responsible firms use cash as a commitment device to honor implicit commitments to stakeholders. Firms with better social performance hold higher cash balances, especially for firms with social performance related to stakeholders or requiring cash spending. This relation is also stronger for firms that benefit more from social performance, e.g., firms that face more competition in product and labor markets. Social performance related to stakeholders or requiring cash spending increases the marginal value of cash.